Determinan Pemberian MP-ASI pada Balita 6-24 Bulan di Desa Murnaten Kabupaten Seram Bagian Barat - Trixie Leunupun; Adriana Sainafat; Yohana Djurumana (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
Complementary feeding (MP-ASI) is provided as a supplement to meet the nutritional needs of infants that can no longer be optimally fulfilled by breast milk alone. As a supplement to breast milk, MP-ASI plays an important role in supporting the growth and development of infants after reaching six months of age. Although breastfeeding is recommended to continue until the child reaches two years old, various factors such as maternal knowledge, attitudes, and habits greatly influence MP-ASI feeding practices. Based on data from the 2018 Basic Health Research (Riskesdas), only about 35% of infants in Indonesia received exclusive breastfeeding, while the practice of providing complementary foods was recorded at 45%. The low level of parental knowledge regarding proper MP-ASI practices is suspected to be related to factors such as education level, limited access to information, and strong cultural influences. These have become the main challenges in promoting appropriate MP-ASI practices. This study aimed to identify the factors influencing the provision of complementary feeding among children aged 6–24 months in Murnaten Village, West Seram Regency. The study used a cross-sectional design with a total sampling technique, involving all mothers with children aged 6–24 months, with a total of 40 respondents. The results showed a significant relationship between maternal knowledge, attitudes, and habits with MP-ASI feeding practices (p < 0.005).